2016
DOI: 10.3892/mmr.2016.4853
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in hypertensive brain damage in the hippocampi of spontaneously hypertensive rats

Abstract: The aim of the present study was to investigate the age-related alterations in hypertensive brain damage in the hippocampi of spontaneously hypertensive rats (SHR) and the underlying mechanisms. Aging resulted in a significant increase in the number of activated astrocytes and apoptotic cells in the SHR group, which was accompanied by increased expression of oxidative stress markers (iNOS and gp47phox) and apoptotic regulatory proteins (Bax and caspase-3). In addition, the expression of PPAR-γ and Bcl-2 were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Long term L-2286 treatment aided preserving structure of vessels in this area. Compromised barrier function and perturbations in the supply of neuronal tissue leads to the activation of astroglia population evident in young SHR animals by the elevated expression of GFAP in different brain areas, compared to their normotensive counterparts [36, 38, 74]. Regarding this process, in our study we found an increase in the average size of reactive astrocita in the hippocampal fissure of SHR-C animals (Fig 3H), without hyperplasic differences between the strains.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Long term L-2286 treatment aided preserving structure of vessels in this area. Compromised barrier function and perturbations in the supply of neuronal tissue leads to the activation of astroglia population evident in young SHR animals by the elevated expression of GFAP in different brain areas, compared to their normotensive counterparts [36, 38, 74]. Regarding this process, in our study we found an increase in the average size of reactive astrocita in the hippocampal fissure of SHR-C animals (Fig 3H), without hyperplasic differences between the strains.…”
Section: Discussionsupporting
confidence: 52%
“…Brains of SHR animals show well-described pathologies related to chronic hypertension, which make these animals a feasible model for studying target organ damages [36, 74]. A vasogenic oedema related dilatation of the cerebral ventriculi was observed [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the affected regions, the hippocampus appears to be highly vulnerable to hypertension. Thus, typical findings in SHR hippocampus include neuronal degeneration, necrosis and apoptosis, amyloidosis and tau pathology, atrophy of dendrites, low spine number and abnormal neurogenesis . Hippocampal damage accelerates with time, as shown by increased oxidative stress and expression of apoptotic markers in the hippocampus of ageing SHR .…”
mentioning
confidence: 99%
“…Thus, typical findings in SHR hippocampus include neuronal degeneration, necrosis and apoptosis, amyloidosis and tau pathology, atrophy of dendrites, low spine number and abnormal neurogenesis . Hippocampal damage accelerates with time, as shown by increased oxidative stress and expression of apoptotic markers in the hippocampus of ageing SHR . In the hypothalamus, SHR show increased expression of the hypertensinogenic peptide arginine vasopressin and its V1b receptor, contributing to hypertension impairment .…”
mentioning
confidence: 99%